Going concern assessment: a literature review (The Journal of Forensic Accounting Profession, 2024)
This paper addresses a underlying assumption of financial statements: going concern assumption. The going concern assumption constitutes a foundational premise presuming that the entity will conduct its operations in the forthcoming period (at least 12 months) without significant risk of business interruption. The primary objective of financial reporting is to provide information regarding the entity's financial position and performance to diverse users. Management is obligated to apprise users, and auditors are tasked with scrutinizing the assertion that the entity will continue its operations for a period exceeding 12 months. This paper meticulously examines the regulatory framework grounded in International Financial Reporting Standards and International Standards on Auditing. It particularly scrutinizes the role and significance of auditors in assessing the going concern assumption, encompassing an analysis of factors influencing the auditor's opinion on the going concern assumption and addressing criticisms directed at auditors. Furthermore, the paper explores past experiences in developing models for evaluating going concern assumptions, potentially aiding forensic accountants in uncovering irregularities in financial statements, given the correlation between a heightened bankruptcy risk and fraudulent activities.(Previously published on Sciendo: https://sciendo.com/article/10.2478/jfap-2023-0009, pod licencom CC BY-NC-ND 4.0)
Keywords: going concern; financial statements; bankruptcy; forensic accounting; bankruptcy models